Use of GPS at research of roads & a vehicle - D. V. Mishuta; V. G. Мikhailov; M. V. Sirai (Системный анализ и прикладная информатика)
The purpose of this work are consideration of use of GPS for a research of roads and modeling of the vehicle/wheel machines (WM).Implementation for this problem of the measuring registering complex on a basis the Raspberry Pi 3/4 minicomputer, the GN-803G sensor and creation of the software in the language C/C ++ is considered.The obtained information about GPS and approaches of selection of necessary data from the messages on the basis of the NMEA 0183 standard submitted in the text ASCII form with the fields divided by a comma is analyzed. An assessment of opportunities of use of the obtained information is given.The scheme of connection of the GN-803N module to Raspberry 3/4 through the GPIO protocol is developed and proved.Reduction of the obtained data to a constant step with use of a polynom of Lagrange of the 2-nd order on three points of a variable step is considered.It is recommended at further use of this corrected data array in process modeling of the car application of a method of interpolation CatMull-Rom on the 4-th points at the fixed step. Program fragments are given in C/C ++.It is offered in the territory of RB during the determining of relative distances and a binding to cards at conversion it is possible to use the simplified linear formula lat_m= 112297,6196∙ Ddec lat , lon_m= 63215,444 ∙ Ddec lon .The offered technique of application of GPS, software, received data are planned to be used for a research of influence of the driver and road conditions on the movement of the vehicle and the subsequent their application when modeling in Matlab/ Simulink, and also in problems of preliminary debugging of management systems by self-driving vehicles.